Regional differences in access to hematopoietic stem cell transplantation among pediatric patients with acute myeloid leukemia. Issue 7 (23rd April 2020) - Truong, Tony H; Pole, Jason D; Bittencourt, Henrique; Schechter, Tal; Cuvelier, Geoff D. E.; Paulson, Kristjan; Rayar, Meera; Mitchell, David; Schultz, Kirk R.; O'Shea, Debbie; Barber, Randy; Sung, Lillian
Abstract: Introduction: Indications for hematopoietic stem cell transplantation (HSCT) in pediatric acute myeloid leukemia (AML) are primarily dependent on risk stratification at diagnosis and relapse status. We sought to determine whether access to HSCT is influenced by regional and socioeconomic factors. Methods: Children with newly diagnosed AML aged < 15 years between 2001 and 2015 were identified using the Cancer in Young People in Canada national population–based registry. Factors potentially associated with the receipt of HSCT were studied using univariate and multivariable logistic regression models. Results: Overall, 568 children with newly diagnosed AML were included and 262 (46%) received HSCT. A greater proportion of patients, 103/157 (65.6%), underwent HSCT after first or subsequent relapse compared to 159/411 (38.7%) patients who underwent transplant before relapse. Among patients for whom HSCT would be considered before relapse, factors associated with higher odds of HSCT in a multivariable analysis were: poor versus good‐risk cytogenetics (Odds ratio [OR]: 30.0, 95% confidence interval [CI]: 7.7–117.0), diagnosis during 2012–2015 versus 2001–2006 (OR: 3.2, 95% CI: 1.6–6.3), diagnosis in eastern Canada versus central Canada (OR: 3.7, 95% CI: 1.9–7.3), and age 10–14 years versus age < 1 year (OR: 5.4, 95% CI: 2.3–12.8). Among patients for whom HSCT would be considered after first relapse, higher odds of HSCT was associated with diagnosis at a HSCT center (OR: 2.1, 95% CI: 1.1–4.1). Conclusion: Patients diagnosed at a HSCT performing center and patients from eastern Canada had higher odds of receiving HSCT. This may suggest preferential access to HSCT for certain patients.